Moma Titanium Minerals Mine, Mozambique - Mining Technology | Mining News and Views Updated Daily - Mining Technology (Mining-technology, 2021)
Moma, one of the world’s biggest titanium mineral deposits, is located 160km from the city of Nampula in Mozambique, Africa. It is owned and operated by Kenmare Resources. The mine contains the titanium minerals ilmenite, rutile and zircon, which are used as feedstock to produce titanium dioxide pigment. It started production of heavy mineral concentrate (HMC) containing these three minerals in April 2007. It produced 1,201,100t of HMC and shipped approximately 853,100t of finished products in 2020. Kenmare carried out an expansion at the mine ten years ago to fulfil the growing demand for titanium dioxide feedstock in the market. The expansion was aimed to increase the design capacity of the mine by 50% while increasing the mine’s reserve estimate and annual production of HMC. Construction work on the expansion began in December 2010 and the works were completed in December 2013. The expanded mine has a mine life of more than 100 years. The first shipment of concentrated mineral sands was dispatched from Mama in Q2 2019, following the commissioning of the product stream in Q4 2018. The Moma mine had more than 1,420 employees at the end of 2019.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - english / inglês; extractive industries / indústrias extractivas; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais

The presource curse in Africa: Economic and political effects of anticipating natural resource revenues - Frynas, Jedrzej George; Buur, Lars (The Extractive Industries and Society, 2020)
The notion of the ‘resource curse’ suggests that large inflows of extractive industry revenues cause many adverse macro-economic and political effects. The resource curse literature focuses on the impact of actual inflows of extractive resource revenues. However, anticipation of future resource revenues can also lead to negative macro-economic and political effects even before resource extraction takes place, which points to the role of behavioral aspects of the ‘resource curse’. Using empirical evidence from three African countries, this article investigates to what extent the anticipation of future extractive revenues led to ‘presource curse’ effects. It finds that all three countries experienced negative effects as a result of anticipation of future extractive revenues, including economic growth volatility, higher levels of national debt, eroded governance and societal conflicts. Given the phenomenal increase in oil, gas and metal ore exploration across Africa, it is likely that many countries experience the negative effects of a presource curse without natural resource extraction or long before natural resources are actually extracted.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; extractive industries / indústrias extractivas; natural resources / recursos naturais

Extractive Industry Transparency Index 2019-2020 - Mapisse, Inocência; Mate, Rui; Cortez, Edson (Centro de Integridade Pública (CIP) / Public Integrity Centre, 2020)
The extractive industry, particularly the oil and gas sector, has proved promising in the Mozambican economy with potential to contribute to economic growth. It is expected that in the next 3 years the country will show growth in the order of two digits. However, in order to ensure the transmission of growth to economic development based on the exploitation of these resources, there are aspects that should not be ignored such as transparency in governance in the sector. This aspect is also recognized by the government of Mozambique through the Report on Transparency, Governance and Corruption published in July 2019, which emphasizes that the opacity in this sector can give rise to serious conflicts of interest and harm the perception of the population about the real benefits that this industry provides to the country. Although the country is part of the Extractive Industry Transparency Initiative (EITI), whose focus is on the reconciliation of payments made by companies and receipts reported by the Government in the extractive industry sector, there is a gap regarding detailed information on several aspects: tax, social, governmental and other equally relevant and that should be made available on a project-by-project basis.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais; transparency / transparência

War in resource-rich northern Mozambique – six scenarios 2020.pdf - Santos, F. A. dos (Chr. Michelsen Institute, 2020)
Since the October 2017 attacks by alleged Islamist insurgents, commonly referred to as Ahlu Sunnah Wa-Jama and locally know as Al Shabab, on Mocimboa da Praia, it has not been entirely clear who the attackers were, what their strategic objectives are and on whose domestic and international support they rely. This paper, grounded in a historical understanding of conflict in northern Mozambique’s Cabo Delgado Province, seeks to identify possible stakeholders and scenarios in what we no longer see as an insurgency, but a war.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais

Mozambique - Invest in the Energy Sector of Mozambique - African Oil and Power (Africa Oil and Power, 2020)
Since initial exploratory drilling in 2007 by U.S. operator Anadarko, Mozambique has uncovered vast natural gas volumes within its offshore basins, and now carries the potential to be the fourth largest natural gas exporter globally. With discoveries ranging from Anadarko’s initial 480 feet of gas found in Area 1 in 2010, to Eni’s discovery of 425 billion cubic meters one year later, the onus now lies on major operators including Royal Dutch Shell, Total, Eni and more to develop the requisite infrastructure to exploit the reserves, generate exports and bring revenue into the country. Potential inhibitors to the development of such resources include two ‘black swan’ events that have occurred since early-2020. In addition to the onset of COVID-19 in March – including a specific outbreak on Total’s Mozambique LNG development – the gas-rich Cabo Delgado province is facing a growing Islamist insurgency that began in the country in 2017. Nevertheless, the world-class nature of Mozambique’s gas assets has offset such inhibitors, and the country recently secured the largest foreign direct investment in Africa to date through its Mozambique LNG development. Gas monetization projects push forward on schedule, as the nation continues on its path to becoming a global energy giant.
Keywords: G - Mozambique / Moçambique; L - english / inglês; infrastructure - energy / infrastrutura - energia; natural resources / recursos naturais

Independent Report of the Extractive Industries Transparency Initiative - EITI (Extractive Industries Transparency Initiative (EITI), 2019)
This is the ninth report reconciling payments made by companies operating in the extractive industry and receipts from the State. 97% of tax revenues from the extractive industry were reconciled. The differences between the payments by the companies and the receipts from the State correspond to 0,17% of the amounts confirmed by the State in 2019
Keywords: *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; extractive industries / indústrias extractivas; natural resources / recursos naturais

Islamic Insurgency in Cabo Delgado: Extractive Industry, Youth Revolt and Global Terrorism in Northern Mozambique - Bonate, Liazzat J. K. (The University of the West Indies, St Augustine, 2018)
The violent insurgency in northern Mozambican province of Cabo Delgado, that started in October 2017 and is still ongoing, caught the government of the country and the public by surprise. Although this insurgency remains largely unexplored and little understood, the only study done so far has suggested that it is being carried out by Muslim youth connected to Islamic radicalism, in particular to the Harakat alShabaab of Somalia and its offshoots in Kenya, Tanzania, and as far as DRC.1 Islam has a long history in Mozambique, since probably the eighth century.2 According to the 2017 National Population Census, Muslims account for about 18% of the total population the country and 58% of the Cabo Delgado inhabitants. However, Mozambique had never had any visible Islamist radical political movement before.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais; youth / juventude

The Project for Supporting the Promotion of Nacala Corridor Development - Final Report - Japan International Cooperation Agency (JICA) (Japan International Cooperation Agency (JICA), 2018)
Final JICA report on Nacala Corridor Development Project, whose objectives include: to clarify organizations for promoting and coordinating the implementation of development strategies for the Nacala Corridor Region in accordance with PEDEC-Nacala and to prepare for the implementation of high priority projects in accordance with PEDEC-Nacala. The study project commenced in April 2012 and the final study report was produced in April 2015.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - Nacala; G - central / centro; G - north / norte; GD - Lichinga; GP - Cabo Delgado; GP - Nampula; GP - Niassa; GP - Tete; GP - Zambézia; L - english / inglês; development partners / parceiros de cooperação; extractive industries / indústrias extractivas; infrastructure / infrastrutura; natural resources / recursos naturais; private sector / setor privado

“Our Lives Mean Nothing” - The Human Cost of Chinese Mining in Nagonha, Mozambique - Amnesty International (Amnesty International, 2018)
This report examines Haiyu’s conduct including what the company did or failed to do in acquiring the right to land for use of mining activity in Nagonha, what it did or failed to do in its operations in Nagonha, and what it did or failed to do in response to the villagers’ demand for compensation and resettlement following the flood. The report looks specifically at the breach of the right to adequate housing and decent living standards ensuing from Haiyu’s destruction of the wetland, and the related destruction of one-fifth of the village by the freak flood. The report also examines the Mozambican Government’s failure to protect, promote and fulfil the right to adequate housing and living standards in the village of Nagonha.
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; natural resources - mining / recursos naturais - mineração; poverty / pobreza

Elite capture and the development of natural resource linkages in Mozambique - Buur, Lars; Monjane, Celso Marcos (Fairness and Justice in Natural Resource Politics, 2017)
This chapter explores these broader processes from the perspective of linkage creation in Mozambique related to mega-projects in natural resource extraction and development from a political economy perspective. From a resource fairness perspective, linkage creation is essential as it allows for a more fair distribution of opportunities for local firms to gain from large-scale natural resource investments and for learning and spillover effects to other parts of the economy. In a longer term perspective, it is a potential key source of economic transformation towards higher value added activities and more and better local employment, therefore reducing dependence on resources.
Keywords: FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; natural resources / recursos naturais

Overblown expectations of the mining sector - Economist Intelligence (Economist Intelligence, 2016)
The government of Mozambique remains confident that its mining boom is set to accelerate in the coming years, despite weak sentiment in the global mining industry. Rising coal production and an eventual rebound in global prices will spur some growth in Mozambique's mining sector in 2016‑20 but we expect that, weighed down by infrastructure deficits and non-competitive policies, it will remain a relatively small contributor to GDP growth. Mozambique has untapped coal reserves estimated to be in excess of 20bn tonnes, as well as commercial quantities of aluminium, gold, titanium, graphite and gemstones. Plus, it benefits from a long coastline and geographic proximity to mineral-hungry markets in Asia. At the peak of the commodity super-cycle, investor interest in Mozambican mining soared; the contribution of the mining sector to GDP increased from 1.6% in 2009 to 3.2% in 2013, while government earnings from the sector swelled from US$40m in 2009 to over US$1bn in 2014.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; extractive industries / indústrias extractivas; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais

Strategy for Sweden’s development cooperation with Mozambique, 2015–2020 - Ministry for Foreign Affairs - Sweden (Ministry for Foreign Affairs - Sweden, 2015)
Within the framework of this strategy, Swedish development cooperation with Mozambique aims to make use of the increased interest and potential to utilise the country's natural resources in a socially, economically and environmentally sustainable way. It also aims to improve opportunities for people living in poverty to contribute to and benefit from economic and democratic development. The strategy is valid for the period 2015–2020 and comprises a total of SEK 4.1 billion.
Keywords: G - Mozambique / Moçambique; L - english / inglês; economic development / desenvolvimento económico; natural resources / recursos naturais

Gas for development or just for money? - Hanlon, Joseph; Nuvunga, Adriano (Centro de Integridade Pública (Public Integrity Centre), 2015)
Mozambique’s gas can be used to promote industrialisation and rural development, but only if key choices are made now. Current priorities are for export based mega-projects promising high revenues, but like past mega-projects doing little to create jobs or reduce poverty. Mega-projects costing tens of billions of dollars are essential, but the Council of Ministers can instruct that negotiations give a higher priority to using the gas to create a domestic industry and jobs, even if it reduces short term income.
Keywords: *indexed; *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais; rural development / desenvolvimento rural

Natural Gas and Socio-Economic Transformation in Mozambique: Some Preliminary Evidence - Uetela, Pedro; Obeng-Odoom, Franklin (The Journal of Energy and Development, 2015)
The aim of this article is to extend the state of analysis on the impacts of gas development in Mozambique by evaluating the relationship between the gas sector, the Mozambican economy, and social change. As the resource curse framework is only limited to economic growth, this work utilizes two alternative frameworks—the Staples approach and the Linkages approach—that are melded into an institutional analysis, looking simultaneously at “benefits, costs, and uncertainties” or “blessings, uncertainties, and curses,” and used to conceptualize progress more widely to include not only growth, but other externalities and broader social change as applied to the case of Mozambique. In so doing, the evidence suggests that the natural gas industry in Mozambique has contributed to both the expansion in economic growth and social change. However, the positive experience with social change arises from direct intervention and not necessarily the result of the related economic growth. Indeed, in the process of economic growth, the production and export of natural gas in Mozambique have raised the possibility of major socio-economic and ecological dangers. Contrary to the theoretical criticism of spending windfall revenues on social services as wasteful, we argue that only strategic social and ecological expenditures of gas revenues can provide and increase the chances of the gas industry becoming transformational economically, socially, and ecologically. The article is organized as follows; the next section deals with conceptualizing the paper and describing the sources of data. This is followed by sections that present the results, a discussion of those results, and conclusions and policy implications from the study.
Publisher: International Research Center for Energy and Economic Development (ICEED)
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; economic development / desenvolvimento económico; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais; ⛔ No DOI found

APRM Country Review Report Mozambique - República de Moçambique (República de Moçambique, 2009)
The major cross-cutting issues which featured prominently in all the thematic areas are highlighted below. A comprehensive approach is needed to address these issues as they have wider ramification for the various dimensions of governance in Mozambique. The following are the major thirteen crosscutting issues emerging from this report: Poverty and Inequality; Party/government/business dichotomy; HIV/AIDs; Land Ownership; High levels of illiteracy; High aid dependency; Information flow and paucity of data; Inclusivity; Crime, safety and Security; Domestic violence; Capacity constraints and implementation challenge; Elections; and, Corruption. CONCLUSION: The remarkable recovery that Mozambique has made since the end of the civil war in 1992 should make the people proud of their accomplishments. Over the last two decades, Mozambicans has made considerable progress in rebuilding its political, economic and social institutions, with noticeable progress. There is no doubt that Mozambicans can build on the successes highlighted in this report, while addressing the challenges in a vigorous manner, in order for the country to rapidly move forward. With its abundant natural resources, Mozambicans can exploit these resources for the benefit of the majority of its people. But this will be difficult to achieve without pragmatic and innovative solutions to the challenges arising from both the thematic and cross-cutting issues identified by this report.
Keywords: *non-public; G - Mozambique / Moçambique; L - english / inglês; conflict - civil war / conflito - guerra civil; governance / governação; health / saúde; natural resources / recursos naturais; poverty / pobreza

Institutional Change and Community Based Natural Resource Management in Northern Mozambique - Anstey, Simon (University of Zimbabwe, 2009)
The objective of this study is to examine how the extensive institutional change of reforms to policy and legislation in Mozambique over the past decade has affected evolutions at the local level in the governance of natural resources. The particular focus of the research is an analysis of a community based natural resource management (CBNRM) initiative in North Sanga District of Niassa Province and a longitudinal study of its development between 1999 and 2007 based on my involvement as both field practioner and researcher. The research reveals institutional change in the governance of natural resources by communities in North Sanga as non-linear, non-equilibrium and scale interactive; as well as the agency in change being contingent on specific contexts (historical, social and environmental) and responsive to the beliefs of the actors involved. The importance of ‘crisis’ in promoting new cycles of adaptation for local governance is emphasised as is the significance of gaining formal ownership of the land by the community in acting as a key promoter of their agency in institutional and governance change.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; governance / governação; land governance / gestão de terra; natural resources / recursos naturais

Mineral Resources Potential in Mozambique - Lehto, Tapio; Gonçalves, Reinaldo (Geological Survey of Finland, 2008)
The metallic mineral, industrial mineral and construction material resources in Mozambique have been mapped as part of the Mineral Resources Management Capacity Building Project, financed by a grant provided by the Nordic Development Fund. A database covering the location and characteristics of more than 600 mineral indications, showings and deposits within the geographical contract area assigned to the GTK Consortium was created. A total of 140 mineral occurrences were selected for field surveys and assessments that were mainly carried out during May-November 2003, 2004 and 2005. All available data in the report archives of the client, the National Directorate of Geology (DNG), was collected and transferred to the mineral occurrence database, which was then updated with information from field surveys and with new data published by exploration and mining companies on the Internet. New mineral resources maps at the scales 1:50 000 (part of contract area), 1:250 000 and 1:1 million were prepared with the corresponding symbols for various commodities plotted. Favourability maps showing zones with high potential for selected commodities were compiled at the 1:250 000 scale. The mineral resources in Mozambique were described in the four map explanation volumes and summarized in the final reports for the projects Geological Mapping LOT 2 and Geological Mapping LOT 3. As a consequence of increased geological knowledge, facilitated by the activities of the GTK Consortium, investments in Mozambique’s mineral potential by leading international and regional mining companies is already increasing. Currently, global mining houses are investing in exploration for energy minerals (hydrocarbons, coal and uranium), for titanium and zirconium in heavy mineral sands, for gold and gemstones, for the agricultural minerals lime and phosphate and for tantalum, fluorite and other industrial minerals.
Keywords: G - Mozambique / Moçambique; L - english / inglês; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais; ⛔ No DOI found

Exploring Natural Resources in Mozambique: Will it be a Blessing or a Curse? - Bacuane, Aurélio; Mulder, Peter (Instituto de Estudos Sociais e Económicos (IESE), 2007)
Mozambique has considerable quantity of natural resources, of which the major part is yet to be explored. The Government of Mozambique is determined to extract and export its natural resource potential as soon as possible, supposing that this will positively contribute to economic growth and poverty reduction. However, any resources rich countries are among the poorest nations in the world, in spite of decennia-long exploration of their natural wealth. This so colled 'paradox of plenty' or 'resource curse' raises the question whether the foreseen exploration of natural resources in Mozambique will pose a serious threat rather than a blessing to its economic development. In this paper we first estimate the potential resource wealth of Mozambique in comparison to other countries. Next, we briefly review the rowing body of literature on the existence and determinants of a natural resource curse. Then we evaluate the risk of a resource curse to occur in Mozambique in the (near) future. Finally, we try to come up with suggestions to avert a Mozambican resource curse.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); extractive industries / indústrias extractivas; institutions / instituições; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais; transparency / transparência

The resource curse: which institutions matter? - Kolstad, Ivar; Chr. Michelsens institutt (Chr. Michelsen Institute, 2007)
Two types of models are dominant in the current resource curse literature. One type of model studies the selection of entrepreneurs into rent-seeking versus productive activities. The other type analyses the use of patronage by politicians seeking re-election. The policy implications of the two models are quite different. The first model suggests that institutions governing the private sector ought to be improved. The second model suggests that institutions governing the public sector should be emphasized. This article empirically tests the impact of the private versus public sector institutions on the resource curse, using cross-country data from Sachs and Warner (1997a) and Polity IV. The main result is that only improved private sector institutions ameliorate the resource curse.
OCLC: 191689446
Keywords: L - english / inglês; institutions / instituições; natural resources / recursos naturais